Analysis of culture shock in intercultural communication studies : (Case study of Students from Banggai Islands communication science study program, faculty of social and Political Sciences, University of Muhammadiyah Luwuk) - nada rahmi, Nada Rahmi Safira Julyanti; ken amasita, Ken Amasita Saasdjad; suanti tunggala, Suanti Tunggala (COMMICAST, 2022)
This study aims to determine how proud students of the Archipelagic Communication Studies Program, Faculty of Social and Political Sciences, Muhammadiyah University, Luwuk, face culture shock. The method used in this study is a mix method that combines descriptive qualitative and quantitative data analysis and the data sources are primary data and secondary data. While the sample and population amounted to 14 people using sampling techniques, namely observation, questionnaires and documentation. For data analysis in this study using qualitative descriptive data analysis techniques that use tables of distribution of respondents' responses which are then explained based on phenomena at the research site. The results showed that the respondents were able to pass the stage of culture shock well and showed the final percentage of 75.09%.